Answer:
(g+f)(x)=(2^x+x-3)^(1/2)
Step-by-step explanation:
Given
f(x)= 2^(x/2)
And
g(x)= √(x-3)
We have to find (g+f)(x)
In order to find (g+f)(x), both the functions are added and simplified.
So,
(g+f)(x)= √(x-3)+2^(x/2)
The power x/2 can be written as a product of x*(1/2)
(g+f)(x)= √(x-3)+(2)^(1/2*x)
We also know that square root dissolves into power ½
(g+f)(x)=(x-3)^(1/2)+(2)^(1/2*x)
We can see that power ½ is common in both functions so taking it out
(g+f)(x)=(x-3+2^x)^(1/2)
Arranging the terms
(g+f)(x)=(2^x+x-3)^(1/2) ..
Do you still need the answer, because im working on the same question..
ANSWER:
x° = 24°
y° = 72°
Analysis on picture hope it helps
Answer:
3m - 4
Step-by-step explanation:
Divide.
(15mn)/(5n) = 3m
(-20n)/(5n) = -4
3m - 4 is your answer.
~